Prolonged bleeding due to hirudotherapy (medicinal leech therapy) - Isa MH; Lim, Kristina Hoong Yew; Abd-Samat AH (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Medicinal leech therapy is a form of complementary medicine that has long been practised and is gaining popularity in recent years for various illnesses and surgical applications. However, leech saliva contains proteins with anticoagulant properties that can lead to prolonged bleeding from the bite area. We report a case of a 35-year-old male who presented to the Emergency Department due to prolonged bleeding from a leech-bite wound. He did not have any significant past medical history or medication history. He had undergone medicinal leech therapy for chronic back pain. After the therapy, he noted that the bleeding did not stop after 7 hours (which normally stops within 30 minutes) and decided to seek treatment. There were wounds over his lower back and both feet, which were all clean. The wound over the lower back had persistent oozing. We applied topical adrenaline and manual compression on the wound, and eventually the bleeding reduced and stopped. There are many suggested methods to stop bleeding from leech-bite wounds but there is scarcity of evidence regarding the superiority of any method. This is the first case report regarding bleeding complications in medicinal leech therapy in Malaysia. This report aims to raise awareness regarding the complications arising from a leech bite among the practitioners of medicinal leech therapy, the public and healthcare providers in emergency facilities. We also suggest using topical adrenaline as an alternative to help stop bleeding from leech-bite wounds.